PENGARUH VIRTUAL EXPERIENTIAL MARKETING TERHADAP ONLINE PURCHASE INTENTION DAN E-SATISFACTION - Fabiola Bulimasena Luturmas; Maulita; Amir Hidayat (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This study aims to determine the effect of Virtual Experiential Marketing variables on Online Purchase Intention and e-Satisfaction in e-commerce users specifically in the Samarinda area. The sampling technique is purposive sampling by distributing questionnaires via google form and there are 56 valid questionnaires processed with SmartPLS. The results of this study found that Virtual Experiential Marketing has a significant positive effect on Online Purchase Intention, Virtual Experiential Marketing has an effect on e-Satisfaction and Online Purchase Intention has a significant positive effect on e-Satisfaction.